2007
DOI: 10.1128/jvi.02312-06
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Effects of Adenovirus Type 5 Helper Functions on Adeno-Associated Virus Type 5 (AAV5) Protein Accumulation Govern AAV5 Virus Production

Abstract: Full replication of adeno-associated virus type 5 (AAV5) is sustained by adenovirus type 5 (Ad5) helper functions E1a, E1b, E2a, E4Orf6, and virus-associated (VA) RNA; however, their combined net enhancement of AAV5 replication was comprised of both positive and negative individual effects. Although Ad5 E4Orf6 was required for AAV5 genomic DNA replication, it also functioned together with E1b to degrade de novoexpressed, preassembled AAV5 capsid proteins and Rep52 in a proteosome-dependent manner. VA RNA enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…However, as shown in Fig. 1B, and as we have shown previously (7,8,(10)(11)(12), substantial levels of a Rep40-like protein product are generated during both AAV5 and goat AAV infections of 293 cells (Fig. 1B, lanes 1 and 2), despite the relatively low levels (Ͻ5%) of splicing from upstream transcripts (Fig.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…However, as shown in Fig. 1B, and as we have shown previously (7,8,(10)(11)(12), substantial levels of a Rep40-like protein product are generated during both AAV5 and goat AAV infections of 293 cells (Fig. 1B, lanes 1 and 2), despite the relatively low levels (Ͻ5%) of splicing from upstream transcripts (Fig.…”
supporting
confidence: 77%
“…Thus, these viruses would not be expected to generate significant quantities of Rep40. However, immunoblot analyses have consistently demonstrated the presence of significant levels of a Rep40-like (but not a Rep 68-like) protein during AAV5 and goat AAV coinfection with adenovirus, as well as during transient transfection (7,8,11). This suggested that AAV5 may generate a Rep40-like protein using a mechanism distinct from the alternative splicing utilized by AAV2.…”
mentioning
confidence: 99%
“…In addition to these important functions, we have recently shown that E4Orf6 together with E1B-55k can promote the degradation of de novo-generated AAV5 capsid and small Rep proteins (9). We have also shown that one of the important roles that VA RNA plays in promoting AAV5 infection is to overcome the effect that E4Orf6-E1B-55k has in reducing the accumulated levels of AAV5 proteins (9).…”
mentioning
confidence: 99%
“…E4Orf6-E1B-55k-dependent degradation of de novo-generated AAV5 capsid proteins and Rep52 is inhibited by both MG132 and lactacystin (9), suggesting that it occurs in a proteasome-dependent manner, which typically is mediated by ubiquitinylation of target proteins. As shown, E4Orf6-E1B-55k-dependent degradation of both AAV5 capsid proteins (Fig.…”
mentioning
confidence: 99%
“…In the Adeno-Associated Virus type 5 (AAV5), a member of the Dependovirus genus, viral replication and protein synthesis was highly enhanced by the co-expression of an adenovirus VA I RNA (Nayak and Pintel 2007a) that, by binding to PKR, prevents its otherwise activation by a short RNA sequence of AAV5 messengers (Nayak and Pintel 2007b). The infection of untransformed fibroblast cells by MVM of the Parvovirus genus, activated PKR and subsequently phosphorylated eIF2α (Ventoso et al 2010).…”
Section: Translational Control Of Parvovirus Gene Expression In Gliobmentioning
confidence: 99%